Assessing Climate Change and Wildfire’s Impact on Tourism Sustainability and Resilience - Talukder, Mohammad Badruddoza; Kumar, Sanjeev; Swarna, Dil Afrin Swarna; Lina, Farhana Yeasmin (Studia Ecologiae et Bioethicae, 2025)
This paper examines the mounting threats to sustainability and resilience of international tourist destinations resulting from climate change and the increasing frequency of wildfires. The primary focus of this investigation is examining environmental risks and stability of tourist systems while focusing on ecological, economic, and social aspects. Researchers measured industry weaknesses and response plans through qualitative research involving extensive field investigations in wilderness wildfire-prone zones. The researcher collects secondary data and examines case studies that undergo thematic analysis to uncover impact and resistance patterns. Research demonstrates that wildfires cause severe damage to fundamental infrastructure combined with disturbances that limit visitor access and diminish tourism attractions. The adaptation solutions for tourism development include service diversification, early warning systems, and sustainable land management programs involving the community. Investigative research provides touristic establishments with means to enhance their environmental adaptation abilities and deepen their knowledge of climate conditions as regards travel. The research helps expand sustainability dialogues about tourism development in stressful climates by showing management challenges and adaptable solutions that guide climate resilience implementation for politicians, planners, and tourism operators during planning processes. Protective measures for tourist resources and sustainability advancements become possible through preventive measures established by this system.